Hypoxia enhances tenocyte differentiation of adipose‐derived mesenchymal stem cells by inducing hypoxia‐inducible factor‐1α in a co‐culture system. (29th March 2016) - Yu, Yang; Zhou, Yulong; Cheng, Tao; Lu, Xiaolang; Yu, Kehe; Zhou, Yifei; Hong, Jianjun; Chen, Ying
Abstract: Objectives: Tissue engineering is a promising approach for repair of tendon injuries. Adipose‐derived mesenchymal stem cells (ADMSCs) have gained increasing research interest for their potential in improving healing and regeneration of injured tendons. The present study aimed to investigate effects of O2 tension and potential signalling pathways on AMDSC differentiation into tenocytes, in an indirect co‐culture system. Materials and methods: Human ADMSCs were co‐cultured under normoxia (20% O2 ) and also under hypoxia (2% O2 ). Tenocyte differentiation of AMDSCs and expression of hypoxia‐inducible factor‐1 (HIF‐1α) were analysed by reverse transcription‐PCR, Western blotting and immunohistochemistry. Furthermore, HIF‐1α inhibitor and inducer (FG‐4592) effects on differentiation of AMDSCs were studied using qPCR, immunofluorescence and Western blotting. Results: Indirect co‐culture with tenocytes increased differentiation of ADMSCs into tenocytes; furthermore, hypoxia further enhanced tenocyte differentiation of AMDSCs, accompanied by increased expression of HIF‐1α. HIF‐1α inhibitor attenuated effects of hypoxia on differentiation of ADMSCs; in contrast, FG‐4592 increased differentiation of ADMSCs under both hypoxia and normoxia. Conclusions: Taken together, we found that growing ADMSCs under hypoxia, or activating expression of HIF‐1α to be important in differentiation of ADMSCs, which provides a foundation for application of ADMSCs in vivo for tendon regeneration.